Rapid screening of zeolite acidity by thermal response measurements using InfraSORP technology - Werner, Anja; Woellner, Michelle; Bludovsky, Paul; Leistner, Matthias; Selzer, Carolin; Kaskel, Stefan (Microporous and Mesoporous Materials, 2018)
Thermal response measurements using the recently developed InfraSORP technology are nowadays established as a versatile and rapid screening tool for the estimation of physicochemical properties of porous materials, such as adsorption capacity, surface area and porosity. In the present work, InfraSORP experiments are explored for fast screening of zeolite acidity especially for test samples available only in small quantity. Twelve MFI and beta type zeolite samples with varying molar Si/Al ratios were examined using ammonia as test gas (0.5% NH3 in nitrogen). Caused by the exothermic adsorption of ammonia on acidic sites of the zeolite samples, a characteristic temperature response curve (temperature vs. time) is observed. The specific peak area under the curve reflects the total NH3 amount adsorbed. In two consecutive adsorption/desorption runs the contributions of physisorbed and chemisorbed NH3 are distinguished. The difference between the first integral of the thermal response (caused by physisorption and chemisorption of NH3) and a second adsorption cycle (reflecting only weakly adsorbed NH3) correlates directly with the sample acidity determined by conventional temperature-programmed desorption of ammonia (TPD). Calibration of the signal versus established TPD techniques results in excellent correlation and renders the new technique as a promising high-throughput screening tool for zeolite acidity assessment in industrial process and product quality control requiring less than 30 min per sample.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Acidity; High-throughput screening; InfraSORP; Optical calorimetry; Zeolites